Kerukunan Umat Beragama di Denpasar Bali - Saleh, Syamsudduha (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2017)
This paper is based on a research concerning religious harmony in Denpasar Bali. The purpose of this paper is to look at religious life in Denpasar multicultural society, how they coexist with a harmonious life, and how they experience friction due to religious and ethnic differences. This study applies a qualitative method with an interdisciplinary approach comprising anthropology and social sciences. Inter-religious relations in Denpasar reflect a public awareness of the existence of a pluralistic society that has an egalitarian narure with similarities as well as differences in their being creatures of God Almighty. Harmonious life in Denpasar is based on mutual respect and appreciation in among adherents of different religions.